IMPLEMENTASI MODEL ROBOT EDUKASI MENGGUNAKAN MIKROKONTROLER ATMEGA8 UNTUK ROBOT PEMADAM API - Devid Prastyawan; Bambang Eka Purnama; Indah Uly Wardati (UNIVERSITAS STEKOM, 2017)
The urgent needs of the Industry as well as in the field of modernization diera other auto mover due to its limitations of personnel to work directly in the control or perform tasks dangerous or other duties. In addition to many experts in the field of robotic media is required to learn the use of the robot robotics education. Educational Robot was created so that costs are used for learning as well as research becomes much cheaper and affordable. As well as hardware easy to search. In fact a lot of barriers/difficulties faced in the manufacture of fire-based line follower robot finger using the appropriate sensor, mechanical problems or software. Creation robot line follower with ATmega8 Microcontroller-based extinguisher sensor photodioda this can be used as a learning tool or as a basis for the design of more complex robots. One of the most simple educational robots and is the basis of the movement of the robot Robotics line follower (follower line) that can be developed into a line follower robot fire extinguisher.